Upaya Pengenalan Bahasa Arab Dasar dengan Metode Talqin kepada Anak TPQ Ar-Rahmah Dusun Pacet Selatan - Ogi Saputra; Yazid Abdussalam; Slamet Muliono Redjosari (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
Learning Arabic is one way to make it easier to learn, memorize, practice, and understand the contents of the Qur'an. Learning Arabic will also make it easier for us to understand, memorize, explain and practice the traditions of the Prophet ṣallallāhu 'alaihi wa sallam. Therefore, researchers are trying to introduce Arabic to the children of TPQ Ar-Rahmah at South Pacet Village, with the hope of attracting the younger generation and interested in learning Islam more deeply. The problem faced in implementing the program is the lack of motivation and encouragement from parents and the surrounding environment to study religion, it is often found that children are absent from TPQ Ar-Rahmah so that learning is less than optimal. For learning activities, the researcher introduced basic Arabic vocabulary to TPQ Ar-Rahmah students such as vocabulary about body parts and then introduced basic conversations such as self-introduction in Arabic. This program is running smoothly as the main program of KUKERTA STAI Ali bin Abi Talib Surabaya and has shown the planned results that children can get to know Arabic and Islamic knowledge.